Calcein Staining as a Tool to Investigate Coccolithophore Calcification - Fox, Emily; Meyer, Erin; Panasiak, Natalie; Taylor, Alison R. (Frontiers in Marine Science, 2018)
Despite the oceanographic and geological significance of coccolithophores, the cellular mechanisms that underlie the intracellular production and subsequent secretion of their CaCO3 coccoliths remain poorly understood. Tools for labelling coccoliths and coccospheres in order to track their production would be of great value. We therefore evaluated the use of calcein, a derivative of fluorescein, as a method to fluorescently label coccoliths. The calcein method readily labelled pre-existing coccospheres in a range of coccolithophore species, including diploid and haploid life history phases, without compromising the coccolith structure. Calcite staining was verified though epifluorescence and confocal microscopy, and both stained and unstained cells and coccoliths were readily distinguished using flow cytometry. The fluorescence of stained coccoliths was retained for > 3 d allowing us to confirm the polar secretion of coccoliths by distinguishing pre-existing coccoliths from the accumulation and distribution of non-fluorescent coccoliths produced after calcein exposure. The calcein treatment had no significant effect on photosynthetic physiology, external calcite morphology, or growth rates of the cells over an 8 d period. The calcein staining method therefore represents a simple non-invasive, non-toxic optical technique to ‘tag’ calcium carbonate coccoliths and track their production in response to environmental manipulations or pharmacological treatments. Moreover, calcein staining of the coccosphere allowed for heterogenous patterns of calcification, growth, and cell division to be detected in a population of cells. This is the first description of the use of calcein to stain the biomineral structures of calcifying phytoplankton and this approach has the potential to be applied to detailed cytological investigations as well as high-throughput analysis of cultured cells or field populations.